A detailed study on impact of factors on purchases of mobile phones with special reference to gorakhpur - Tripathi, Santosh Kumar (International journal of economic perspectives, 2008)
In this modern era, a wide variety of other services such as email, text messaging, MMS, internet access, audio and video, short-range wireless communications (Inferred, Bluetooth), gaming, etc. are also supported by mobile phones. In addition to these, it also offers more general computing capabilities that are referred to smart phone. In Bangladesh, many mobile phone brands are available e.g. Nokia, Samsung, Sony, HTC, Panasonic, Motorola, LG, Symphony, Micromax, Walton, etc. and consumer choose their preferred mobile phone from this pool. Demographic factors play a vital role in marketing in today’s era. Mobile phones are in demand, one can find thousands of customers using mobile phones in Gorakhpur. This study will be useful for mobile phones manufacturer and sellers. As it is providing key insights on demographic variables affecting consumer buying behavior towards the mobile phone.